2015
DOI: 10.1007/s11605-015-2821-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Harvest During Esophagectomy Is Not Influenced by Use of Neoadjuvant Therapy or Clinical Disease Stage

Abstract: The LNH was not significantly influenced by neoadjuvant treatment or pathologic response. The LNR was inversely related to pathologic response after neoadjuvant therapy. Complete pathologic response to neoadjuvant therapy trends to improve survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A register-based study from the United States on patients undergoing oesophagectomy for gastroesophageal cancers (n = 18,777) suggested that neoadjuvant therapy was associated with a decreased likelihood of obtaining 15 or more nodes, but did not assess specific numbers of nodes 37 . Another register-based study from the United States (n = 5,805), a Taiwanese register-based study (n = 2,151), and a hospital-based study (n = 111) from the United States found no association between neoadjuvant therapy and lymph node yield in oesophageal cancer 14 , 15 , 38 , but none of these studies adjusted the results for surgeon volume, or other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…A register-based study from the United States on patients undergoing oesophagectomy for gastroesophageal cancers (n = 18,777) suggested that neoadjuvant therapy was associated with a decreased likelihood of obtaining 15 or more nodes, but did not assess specific numbers of nodes 37 . Another register-based study from the United States (n = 5,805), a Taiwanese register-based study (n = 2,151), and a hospital-based study (n = 111) from the United States found no association between neoadjuvant therapy and lymph node yield in oesophageal cancer 14 , 15 , 38 , but none of these studies adjusted the results for surgeon volume, or other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized CROSS trial also found that the number of RLNs in patients with EC was significantly decreased after nCRT (18 vs.14, P < 0.001) [5]. However, a study by Luna et al [16] showed that nCRT did not affect the number of RLNs (16.0 vs 15.5, P = 0.57). The current study also did not find that preoperative radiotherapy affected the number of RLNs.…”
Section: Discussionmentioning
confidence: 99%
“…2,92,93 In contrast to rectal carcinoma, the lymph node harvest in an esophagectomy specimen does not appear to be significantly affected by neoadjuvant therapy. 71,94,95 However, the frequency of lymph node metastasis is reduced after neoadjuvant therapy. 83,95 In addition, the distribution of positive lymph nodes may be altered by neoadjuvant therapy with one report finding fewer paracardial lymph node metastases compared with patients treated with surgery alone.…”
Section: Handling Of Treated Esophageal and Esophagogastric Junction mentioning
confidence: 99%